SPORTS AND MODERNITY IN THE EARLY 20TH CENTURY IN URUGUAY: A STUDY BASED ON SPORTSMAN MAGAZINE (1908) - Verónica Gabriela Silva Piovani; Ieda Parra Barbosa Rinaldi; Carlos Herold Junior (Journal of Physical Education)
ABSTRACT This study aimed to analyze the relationship between sports and the Uruguayan society in the early 20th century. It was conducted on the basis of cultural history. As sources, 26 issues of Sportsman magazine published in 1908 were used. For document analysis, two thematic units were evidenced: 1) “The role of sports in building a civilized nation”, which identified aspects related to sport practice as important elements for the development of civilization/the nation, and 2) “Sports and the population’s health”, which provided records on sports and their positive impact on health and race. It is concluded that sports stood as a relevant social practice for the copywriters and readers of Sportsman magazine, being fundamental in the construction of a civilized nation.